Translating the Symptom Screening in Paediatrics Tool (SSPedi) into North American Spanish and Among Spanish-speaking children receiving cancer treatments: evaluating understandability and cultural relevance in a multiple-phase descriptive study. Issue 11 (12th November 2020) - Plenert, Erin; Grimes, Allison; Sugalski, Aaron; Langevin, Anne-Marie; Nieto, Dominica; Salaverria, Carmen; Gomez, Sergio; Gonzalez, Gisela; D'Angelo, Gisela; Dupuis, Lee; Sung, Lillian
Abstract : Objectives: Symptom screening is important to achieving symptom control. Symptom Screening in Paediatrics Tool (SSPedi) is validated for English-speaking children. Objectives were to translate SSPedi into Spanish, and to evaluate the understandability and cultural relevance of the translated version among Spanish-speaking children with cancer and paediatric haematopoietic stem cell transplant recipients. Methods: We conducted a multiphase, descriptive study to translate SSPedi into Spanish. The first step was to determine whether one Spanish version would be appropriate for both North America and Argentina. Once this decision was made, forward and backward translations were performed. The translated version was evaluated by Spanish-speaking children 8–18 years of age receiving cancer treatments. Primary and secondary outcome measures: Primary outcome was child self-reported difficulty with understanding of the entire instrument and each symptom using a 5-point Likert scale. Secondary outcomes were incorrect understanding of SSPedi items identified by cognitive interviews with the children using a 4-point Likert scale and cultural relevance, which was assessed qualitatively. Results: This report focuses on North American Spanish as a separate version will be required for Argentinian Spanish SSPedi based on different common vocabulary and grammatical structure. There were 20 children from Toronto and San Antonio included in cognitive interviews. The most common types of Spanish spoken were Mexican (13, 65%), Central American (2, 10%) and South American (2, 10%). No child reported that it was hard or very hard to complete Spanish SSPedi. Changes to the instrument itself were not required based on understanding or cultural relevance. Conclusions: We translated and finalised Spanish SSPedi appropriate for use in North America. Future research will translate and evaluate SSPedi for use in Argentina and other Spanish-speaking countries.